Synthesis, Structure and Biological Activity of Amide-Functionalized Titanocenyls: Improving their Cytotoxic Properties - Gao, Li Ming (2009)
Nine amide-functionalized titanocenyls have been synthesized and characterized by spectroscopic and analytical methods and the solid state structure of Cp(CpCO-NH-C(6)H(4)-OCF(3))TiCl(2) was determined by single crystal X-ray diffraction. X-ray analysis of Cp(CpCO-NH-C(6)H(4)-OCF(3))TiCl(2) showed that titanium is in a pseudo tetrahedral geometry and contains a Ti-O(amide) coordination. In principle, Ti-O coordination should provide more hydrolytic stability to the corresponding titanocenyls than titanocene dichloride. The cytotoxic activities of these amide-functionalized titanocenyls on HT-29 colon cancer cell line were determined by MTT assay to elucidate structure-activity relationship. All complexes were more cytotoxic than titanocene dichloride and there is no correlation between the para substituents on the phenyl ring and their cytotoxicities.